Hindenberg and the Weimar Republic - Dorpalen, Andreas (Book collections on Project MUSE., 2015)
Using many unpublished and other primary sources as well as interviews with aides and associates of Hindenburg, the author shows in Hindenburg and the Weimar Republic how this proud and cautious man, naive in politics and preoccupied with his reputation among his fellow generals, failed to act in crucial situations, or hesitated until action was futile. He examines in detail Hindenburg's role during the fateful days when Hitler was forcing his way to the top, scheming to overthrow the republic of which President Hindenburg eventually appointed him chancellor.Originally published in 1964.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.